ANALISIS KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING (Studi Empirik Nasabah Tabungan Tandamata Bank BJB Cabang Serang) - Apriyanti, Putri; Surya, Djasuro; Lutfi, Lutfi (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2017)
The study was conducted by taking samples using Nonprobability Sampling Technique. Samples from 100 BJB Bank Serang branch customers by providing questionnaires consisting of questions and statements. Respondents' answers to questions and statements were analyzed qualitatively and quantitatively, and the answers were analyzed by analytical technique method using SmartPLS version 2.0.m3. The result of analysis shows that the direct influence of service quality to customer loyalty is positive and significant. and the direct influence of corporate image on customer loyalty that is positive and non significant to customer loyalty. then the quality of service to customer satisfaction positive and significant. corporate image to positive and significant customer satisfaction. and customer satisfaction to customer loyalty that is positive and significant.